2016
DOI: 10.3390/molecules21101390
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Related Monoterpenes p-Cymene, Carvacrol and Thymol Isolated from Essential Oil from Leaves of Lippia sidoides Cham. (Verbenaceae) Protect Mice against Elastase-Induced Emphysema

Abstract: Abstract:Background: Chronic obstructive pulmonary disease (COPD) is characterized by irreversible airflow obstruction and inflammation. Natural products, such as monoterpenes, displayed anti-inflammatory and anti-oxidant activities and can be used as a source of new compounds to COPD treatment. Our aim was to evaluate, in an elastase-induced pulmonary emphysema in mice, the effects of and underlying mechanisms of three related natural monoterpenes (p-cymene, carvacrol and thymol) isolated from essential oil f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 77 publications
3
56
0
Order By: Relevance
“…In addition, it promoted the increase in IL‐10, an important anti‐inflammatory cytokine, as demonstrated by Lima et al . Studies with both isomers also reveal that these compounds singly reduce IL‐1β, IL‐6, IL‐8, IL‐17, IL‐25 and IL‐33 . Similar findings were reported by Meeran et al .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, it promoted the increase in IL‐10, an important anti‐inflammatory cytokine, as demonstrated by Lima et al . Studies with both isomers also reveal that these compounds singly reduce IL‐1β, IL‐6, IL‐8, IL‐17, IL‐25 and IL‐33 . Similar findings were reported by Meeran et al .…”
Section: Discussionsupporting
confidence: 82%
“…Carvacrol has been shown to inhibit the expression of IL-4, IL-17 and IL-1b, [38,39] COX-2 [39] and TNF-a. [40] In addition, it promoted the increase in IL-10, an important antiinflammatory cytokine, as demonstrated by Lima et al [39] Studies with both isomers also reveal that these compounds singly reduce IL-1b, IL-6, IL-8, IL-17, [41] IL-25 and IL-33. [42] Similar findings were reported by Meeran et al [43] who demonstrated that thymol is able to decrease the expressions of TNF-a, IL-6 and IL-1b, attenuate the lipoperoxidation and reduce inflammation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For several individual chemical constituents from thyme extract different anti-inflammatory activities have been described. Of these, the terpenol phenols thymol and carvacrol have been most intensively studied with respect to their anti-inflammatory activity [28][29][30]. In addition, the tannin rosmarinic acid, has been described to possess anti-inflammatory activity and also to intervene with eicosanoid production [31].…”
Section: Discussionmentioning
confidence: 99%
“…It reduced the alveolar enlargement, number of macrophages, and levels of proinflammatory cytokines such as IL-1β, IL-6, IL-8, and IL-17 in bronchoalveolar lavage fluid (BALF) (30). Similarly, p-cymene showed a protective effect in a mouse model of LPS-induced acute lung injury by reducing the number of inflammatory cells in the BALF and expression of NF-κB in the lungs (31) and by reducing production of proinflammatory cytokines and infiltration of inflammatory cells (32).…”
Section: Terpenes With Anti-inflammatory Functionmentioning
confidence: 99%